2022
DOI: 10.3389/fphar.2022.936233
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Potential Value of Coenzyme Q10 in Oxidative Stress: Enlightenment From a Synthesis of Clinical Evidence Based on Various Population

Abstract: Background: Oxidative stress (OS) is associated with ferroptosis. Coenzyme Q10 (CoQ10), as an adjuvant treatment, has shown to be beneficial against OS. However, the efficacy of CoQ10 as a therapeutic agent against OS has not been promptly updated and systematically investigated.Methods: A systematic literature search was performed using the Medline, EMBASE, Web of science, Cochrane Central Register of Controlled Trials, CNKI, CBM, Science direct and clinical trial. gov to identify randomized clinical trials e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Previous studies have indicated that CoQ10 has tremendous potential for application in treating musculoskeletal diseases, including RA (Abdollahzad et al, 2015;Jhun et al, 2020) and OA (Chang et al, 2020). In addition, Zhang et al (2022b) reported that CoQ10 could improve oxidative stress, as indicated by the increased MDA concentration. Another report by Yang et al supported the functional regulatory effects of CoQ10 in ferroptosis, controlling sodium iodate-induced pathologies in vitro and in vivo (Yang et al, 2022b).…”
Section: Discussion and Future Remarksmentioning
confidence: 99%
“…Previous studies have indicated that CoQ10 has tremendous potential for application in treating musculoskeletal diseases, including RA (Abdollahzad et al, 2015;Jhun et al, 2020) and OA (Chang et al, 2020). In addition, Zhang et al (2022b) reported that CoQ10 could improve oxidative stress, as indicated by the increased MDA concentration. Another report by Yang et al supported the functional regulatory effects of CoQ10 in ferroptosis, controlling sodium iodate-induced pathologies in vitro and in vivo (Yang et al, 2022b).…”
Section: Discussion and Future Remarksmentioning
confidence: 99%
“…This effect may be attributed to SOD being a potential molecular target of CoQ10. Multiple animal studies, randomized controlled trials and in vitro studies have demonstrated that CoQ10 supplement could improve SOD activity [ 30 , 31 ]. Moreover, plasma oxidative stress markers are significantly elevated in COVID-19 patients, associated with the mechanism of disease development [ 32 ].…”
Section: Discussionmentioning
confidence: 99%